Competition in Costa Rica’s banking industry: an economies-of-scale approach, 1997–2009 - Gutiérrez Li, Alejandro (2013)
I estimate a translogarithmic cost function for the Costa Rican banking industry from which I analyze the presence of economies of scale by bank and market segment (public or private) for the period of 1997-2009. I conclude that the public banks have higher overall economies of scale than the private ones and lower marginal costs in lending. The private segment has higher economies of scale in both services and securities. BAC San Jose and Banco Nacional have the highest economies of scale in the sample.